Peran Raden K.H. Ahmad Masyhud dalam Bidang Dakwah dan Pendidikan di Bandung Tahun 1979-1985 - Ula Hasanah; Mahpuddin Noor; Mahbub Hefdzil Akbar (UIN Sunan Gunung Djati Bandung, 2018)
Raden KH. Ahmad Masyhud is a cleric and founder of the Wanasari al-Istiqomah Islamic Boarding School, founded in 1943. His role is very important in the community especially in the field of Education Da'wah. This study aims to find out the biography of Raden KH. Ahmad Masyhud and the role of Raden KH. Ahmad Masyhud in the field of Da'wah and Education in Bandung. The method used in this research is the historical method. The results of this study show that Raden KH. Ahmad Masyhud, a founder of the Al-Istiqomah Wanasari Islamic Boarding School, had had the ideas to collaborate with friends to establish educational institution. His role in the field of education and da'wah is very influential, especially in the surrounding community. Raden KH. Ahmad Masyhud initially only established a boarding school, but because of his concern for the community, he established a formal education institution. As for the field of Da'wah Raden KH. Ahmad Masyhud managed to spread the teachings of Islam to his surrounding community.